2022
DOI: 10.3390/ijerph19020740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Indications to Germectomy in Pediatric Dentistry: A Systematic Review

Abstract: Germectomy is a procedure often required in patients at developmental age. It is defined as the surgical removal of the third molar at a very specific stage of development. The aim of this study was to systematically analyze the literature in terms of clinical indications for germectomy in patients at developmental age. Literature searches were performed using PubMed, Google Scholar, Cochrane Library and Scopus from 1952 to 30 June 2021. The study protocol was registered after the screening stage (PROSPERO CRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, men’s jaws continue to grow during the eruption of third molars, while women’s jaws stop growing when third molars begin to erupt ( 19 ). Even the indications for germectomy of the mandibular third molar in class III patients have been described in cases where predictors of craniofacial growth reveal excessive anteroposterior mandibular growth, a severe dentoalveolar discrepancy or in cases where distalization of the first and second molars is necessary ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, men’s jaws continue to grow during the eruption of third molars, while women’s jaws stop growing when third molars begin to erupt ( 19 ). Even the indications for germectomy of the mandibular third molar in class III patients have been described in cases where predictors of craniofacial growth reveal excessive anteroposterior mandibular growth, a severe dentoalveolar discrepancy or in cases where distalization of the first and second molars is necessary ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study determined impacted M3s to be associated with impacted M2s, while another study found that M3 germectomy did not benefit the M2 uprighting process. Meanwhile, the authors of the systematic review supported the idea of M3 germectomy in cases of impacted M2 since delaying M3 removal would only put the M2 at greater risk of dental caries or periodontitis and/or complicate M2 eruption 13 . Furthermore, germectomy of M3s was justified to gain space in cases requiring molar distalization.…”
Section: Advantages Of Germectomymentioning
confidence: 99%
“…Most authors defined the tooth in the procedure as having one-third or less of its root 6 , 10 . Recently, a systematic review advocated Demirjian’s classification of types B, C, and D for the definition of germectomy 13 , 15 , 16 . ( Fig.…”
Section: Definitions Of Germectomymentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 Consequently, the number of asymptomatic M3 removals indicated by orthodontists is increasing. 6 However, their ability to predict the prognosis of M3 eruption was inaccurate in approximately 40% of cases. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%